Analyzing Competing Risks with Progressively Type-IICensored Data in Dagum Distributions - Raghd Badwan (21751574) (2025)
Competing risk models are essential in survival analysis for studying systems with multiple mutually exclusive failure events. This study investigates the application of competing risk models in the presence of progressively Type-II censored data for the Dagum distribution, a flexible distribution suited for modeling data with heavy tails and varying skewness and kurtosis. The methodology includes maximum likelihood estimation of the unknown parameters, with a focus on the special case of a common shape parameter, which allows for a closed-form expression of the relative risks. A hypothesis test is developed to assess the validity of this assumption, and both asymptotic and bootstrap confidence intervals are constructed. The performance of the proposed methods is evaluated through Monte Carlo simulations, and their applicability is demonstrated with a real-world example. Other Information Published in: Axioms License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://doi.org/10.3390/axioms14070508